The cooperation of Mongolia and Kalmykia: the present and the future - Namrueva, Lyudmila V. (The New Research of Tuva, 2013)
Article reviews the fruitful relations between the two brother folks – Mongols and Kalmyks – in the fields of education, science and culture.